Korelasi status sosial ekonomi (SES) orang tua dengan prestasi akademik siswa kelas V sekolah dasar - Deni Saputra; Nabila Elyno Putri; Mohammad Edy Nurtamam (Jurnal Pendidikan Dasar, 2025)
Abstract. This study aims to analyze the correlation between parents' socioeconomic status (SES) and the academic achievement of fifth-grade students in Bahasa Indonesia at SD Negeri 9 Jambewangi, an elementary school in Indonesia. Using a quantitative approach with a survey method, data were collected through questionnaires distributed to all fifth-grade students. The Shapiro-Wilk normality test confirmed that the data were normally distributed (SES significance: 0.187; learning outcomes: 0.068). Data analysis included linearity tests, Pearson correlation, and simple linear regression. The results revealed a weak correlation between SES and academic achievement, with a Pearson correlation value of 0.265 and a significance level of 0.340. The regression equation Y = 56.502 + 1.078X + e further indicated that SES does not significantly influence academic performance. The study concludes that while SES may have a slight tendency to affect academic outcomes, its impact is minimal. Factors such as teaching methods, student motivation, and the learning environment play a more significant role in determining academic success. Therefore, it is recommended that schools and educators focus on improving teaching quality, fostering a supportive learning environment, and enhancing student motivation to optimize academic achievement.